Immunotherapeutic Potential of T Memory Stem Cells - Li, Yujie; Wu, Dengqiang; Yang, Xuejia; Zhou, Sufang (Frontiers in Oncology, 2021)
Memory T cells include T memory stem cells (TSCM) and central memory T cells (TCM). Compared with effector memory T cells (TEM) and effector T cells (TEFF), they have better durability and anti-tumor immunity. Recent studies have shown that although TSCM has excellent self-renewal ability and versatility, if it is often exposed to antigens and inflammatory signals, TSCM will behave as a variety of inhibitory receptors such as PD-1, TIM3 and LAG3 expression, and from Metabolic changes from oxidative phosphorylation to glycolysis. These changes can lead to the exhaustion of T cells. Cumulative evidence in animal experiments shows that it is the least differentiated cell in the memory T lymphocyte system and is a central participant in many physiological and pathological processes in humans. It has a good application prospect, so it is more and more important to study the factors affecting the formation of TSCM and tumor immunity. This article summarizes and prospects the biological characteristics and functions of TSCM, the regulation mechanism of differentiation, and its application in clinical tumor treatment.